Respuesta :
Answer:
The equation is a quadratic equation because there is an x2-term.
Step-by-step explanation:
x(x−6)=−5
Distribute
x^2 -6x = -5
The equation is a quadratic equation because there is an x^2-term.
Answer:
Your required answer is option A.
Step-by-step explanation:
Here,
The given equation is;
x(x-6)=-5
now,
while finding x.
either or,
x=-5 (x-6)=-5
x= 1 (shifting-6 in next side)
now, the value of x is -5,1.
so, it's a quadratic equation.
( in quadratic equation the variable always has two values after solution)
Hope it helps..